Social competence of twelfth grade students in public schools and private schools in the Jordanian Madaba governorate: a comparative study - Roslan, Ab Rahman; Khalil Salman, Hassan (2020)
After the researcher noticed the growing and varied manifestations of university violence through the various statistics and media, and on the basis that the most important objectives of science are interpretation of phenomena, prediction and control it, the researcher saw that he may contribute to identify some of the causes and factors for this phenomenon, and provide the decision maker and the school curriculum designer some necessary data, which led to the study of the social efficiency of students in the pre-university stage, the secondary school, in a comparative study between students of public schools versus private schools in Madaba, Jordan, because of importance of the social efficiency of students and their skills and social preparations in the Psychological and social adjustment with the subsequent stage, which is university life. Using a measure of social competence, the researcher built it in four main dimensions and presented it to the specialists for judging it, after applying it to a sample of 400 students, 200 of them were from private schools and 200 from public schools, there were statistically significant differences in the average scores of students in secondary schools between public and private schools on the social efficiency scale in all its dimensions, and from the arithmetic averages, it was found that these differences were in favor of public school students. As well as the existence of statistically significant differences in the average scores of students between males and females on the scale of social efficiency in all dimensions, and from the arithmetic averages show that these differences were in favor of females.